Urban commuters' expectation levels on the e-VTOL vertical airport design in Kuala Lumpur, Malaysia / Raymond Lim Ying Keat, Jestin Nordin and Mohd Najib Mohd Salleh - Ying Keat, Raymond Lim; Nordin, Jestin; Mohd Salleh, Mohd Najib (Universiti Teknologi MARA, Perak, 2021)
The world's urban dwellers are rapidly growing by 60.3% over six decades (1960-2019) (The World Bank Group, 2020), and two third of the world's population is projected to reside in the urban setting by 2050. The same issue occurred in Malaysia, where the shifting from 73% rural to 73% urban population is real (Mohd Hussain, N. H.; Byrd, H.; & Ahmad, N. A., 2017), and this phenomena contributed to the increasing number of population in big cities such as Kuala Lumpur. Therefore, it is expected that the existing challenging traffic congestion will worsen if a better traffic dissemination planning strategy is not developed. Hence, the development of an e-VTOL (electrical vertical take-off landing) vehicle is a possible strategy to ease the urban traffic congestion problem. Serious collaboration among the departments such as planning, engineering, architecture, aviation developers, policy makers, and the sponsors, is important to establish sustainable future urban mobility and connectivity. This study aims to obtain information on the needs and expectations of urban commuters on the development of a vertiport in the city of Kuala Lumpur. A series of surveys involving 157 commuters using public transportation within the city centre, and a case study analysis, were conducted to gain an understanding of the viability of building a vertiport in Kuala Lumpur. Initially, findings show that nearly 50% of the respondents totally agree with the proposed development idea, while approximately 13% are really against this future urban air mobility strategy.